Social Media Big Data Analysis Implementation towards Customer Insight Creation Process in PT. Bank Negara Indonesia (Persero) Tbk. - Farjumzal, Farjumzal; Ashari Nasution, Reza (The Indonesian Journal of Business Administration, 2016)
Abstract. Bank Negara Indonesia (BNI) is one of the leading banks in Indonesia. Currently, BNI provides banking services to 17 million people. BNI followed lifetime banking partner principle. That means that BNI provides banking services that reach out to all kinds of ages and their needs. Customer insight creation is a form of efforts to understand consumer behavior. Thus, customer insight creation is the fundamental aspect in creating unique value for customers. BNI need a broader picture for insight creation in order to creating unique value for its existing and potential customer. The solution chosen by the author in creating unique value for customers is through the implementation of social media big data analytics. BNI could take advantage over its 589,223 Twitter followers. Author utilize Knowledge Fusion Taxonomy concept in order to align the proposed solutions towards existing customer insight creation activities in BNI.Â Keywords: Knowledge fusion taxonomy, social media big data analytics, consumer banking